Effect of Reduction Reaction Temperature on Carbon Purification based on Coconut Shell - Marsi Bani; Djoko H Santjojo; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2013)
The purification carbon from coconut shell through carbonization with pyrolysis method at temperature 600 °C for 1 hour has been done. Carbon is refined in various temperature such as 150 oC, 200 °C, 250 °C, 300 oC, and 350 °C. The flow rate of carbon refining is 200 mL/minute for 1 hour using a reduction reaction method with hydrogen as the reducer to reduce oxygen content in the carbon. The result show indicates that the maximum carbon content 96,53 % at 350 °C. The increasing carbon content during the reduction process because hydrogen attaches oxygen to establish H2O bond and it is proved by the result of FTIR test.